Lower Gastrointestinal Bleeding due to Multiple Polyps in Ileum - Ivo Novita Sah Bandar; Ari Fahrial Syam; Chudahman Manan; Marcellus Simadibrata; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
The causes of lower gastrointestinal bleeding (hematochezia) are amyloidosis, anal fissure, angiodysplastic lesions, coagulation disorder, colitis, colon cancer, colorectal polyps, Crohn’s disease, diverticulitis, haemorrhoids, etc. This was a case of lower gastrointestinal bleeding due to colonic inflammatoric polyp. This inflammatoric polyps were caused by infection/inflammation and improved after antibiotic and NSAID therapy. Key Words : Colonic inflammatoric polyp, hematochezia.